Daytime HONO, NO2 and aerosol distributions from MAX-DOAS observations in Melbourne - Ryan, Robert G.; Frieß, Udo (Atmospheric chemistry and physics, 2018)
Abstract. Toxic nitrogen oxides produced by high temperature combustion are prevalent in urban environments, contributing to a significant health burden. Nitrogen oxides such as NO2 and HONO in pollution are important for hydroxyl radical (OH) production and overall oxidative capacity in urban environments; however, current mechanisms cannot explain high daytime levels of HONO observed in many urban and rural locations around the world. Here we present HONO, NO2 and aerosol extinction vertical distributions retrieved from multi-axis differential optical absorption spectroscopy (MAX-DOAS) measurements in suburban Melbourne, which are the first MAX-DOAS results from the Australian continent. Using the optimal estimation algorithm HEIPRO we show that vertical profiles for NO2 and HONO can be calculated with a low dependence on the retrieval forward model and a priori parameters, despite a lack of independent co-located aerosol or trace gas measurements. Between December 2016 and April 2017 average peak NO2 values of 8±2 ppb indicated moderate traffic pollution levels, and high daytime peak values of HONO were frequently detected, averaging 220±30 ppt in the middle of the day. HONO levels measured in Melbourne were typically lower than those recorded in the morning in other places around the world, indicating minimal overnight accumulation, but peaked in the middle of the day to be commensurate with midday concentrations in locations with much higher NO2 pollution. Regular midday peaks in the diurnal cycle of HONO surface concentrations have only previously been reported in rural locations. The HONO measured implies a daytime source term 1 ppb h−1 above the predicted photostationary state (PSS) concentration and represents an OH radical source up to 4 times stronger than from ozone photolysis alone in the lowest 500 m of the troposphere. The dependence of the high midday HONO levels on soil moisture, combined with the observed diurnal and vertical profiles, provides evidence for a strong photoactivated and ground-based daytime HONO source.